(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the social and psychological factors that shape students’ motivation for professional choice in a modern educational environment. The influence of educational institutions, family, social environment, personal interests and modern digital technologies on the formation of professional motivation is also studied. According to the results of the study, the need for an integrative socio-psychological approach to developing students’ motivation for professional choice is substantiated.